The Effect of Teleeducation Methods on Level Knowledge and Attitudes about HIV/AIDS Student in Ciasem 1 Public High School: Pengaruh Metode Teleedukasi Terhadap Tingkat Pengetahuan Dan Sikap Remaja Tentang HIV/AIDS Pada Siswa SMA Negeri 1 Ciasem - Suciyanti, Suciyanti; Indahwati, Lilik; Iffah A., Krisjentha (Universitas Muhammadiyah Sidoarjo, 2022)
HIV/AIDS is one of the major global health problems. Approximately, 5 percent of all HIV cases are originated from adolescents and around 1.7 million adolescents worldwide are living with HIV in 2019. Adolescents are often less exposed to information related to reproductive health, including HIV/AIDS. The purpose of this study is to determine the effects of the teleeducation method on the level of knowledge and attitudes of adolescents about HIV/AIDS. The research design used in this study was pre-experimental designs with one group pretest-posttest approach. Reproductive health education with the teleeducation method is carried out for 1 day. The data was collected using questionnaires that were distributed before and after the teleeducation was given. The number of respondents that was taken for this study were 78 students who were taken using purposive sampling technique. The results of the non-parametric two-related sample test using the Wilcoxon test in the knowledge analysis showed that the p-value was 0.000 or (p-value < 0.05) and the attitude analysis using the Wilcoxon test found that the p-value was 0.000 or (p-value < 0.05), indicating that there are differences in knowledge and attitudes before and after the teleeducation method was given. It can be concluded from this study that there are effects of the teleeducation method on increasing knowledge and increasing adolescent attitudes about HIV/AIDS.